Respuesta :
[x-1]=5x+10
We have two equations:
1) x-1=5x+10
x-1=5x+10
x-5x=10+1
-4x=11
x=-11/4
2) x-1=-(5x+10)
x-1=-(5x+10)
x-1=-5x-10
x+5x=-10+1
6x=-9
x=-9/6=-3/2
we have two possible solutions:
solution₁; x=-11/4
solution₂: x=-3/2
we check it out:
1) x=-11/4
[x-1]=5x+10
[-11/4 - 1]=5(-11/4)+10
[(-11-4)/4]=-55/4 + 10
[-15/4]=(-55+40) /4
15/4≠-15/4 This solution don´t work.
2) x=-3/2
[x-1]=5x+10
[-3/2 - 1]=5(-3/2)+10
[(-3-2)/2]=-15/2 + 10
[-5/2]=(-15+20)/2
5/2=5/2; this solution works.
Therefore:
Answer: x=-3/2.
We have two equations:
1) x-1=5x+10
x-1=5x+10
x-5x=10+1
-4x=11
x=-11/4
2) x-1=-(5x+10)
x-1=-(5x+10)
x-1=-5x-10
x+5x=-10+1
6x=-9
x=-9/6=-3/2
we have two possible solutions:
solution₁; x=-11/4
solution₂: x=-3/2
we check it out:
1) x=-11/4
[x-1]=5x+10
[-11/4 - 1]=5(-11/4)+10
[(-11-4)/4]=-55/4 + 10
[-15/4]=(-55+40) /4
15/4≠-15/4 This solution don´t work.
2) x=-3/2
[x-1]=5x+10
[-3/2 - 1]=5(-3/2)+10
[(-3-2)/2]=-15/2 + 10
[-5/2]=(-15+20)/2
5/2=5/2; this solution works.
Therefore:
Answer: x=-3/2.
Solution #1 [tex]x-1=5x+10[/tex]
[tex] x-1=5x+10[/tex]
[tex]x-5x=10+1[/tex]
[tex]-4x=11[/tex]
[tex]x=-11/4[/tex]
Solution #2 [tex]x-1=-(5x+10)[/tex]
[tex] x-1=-(5x+10)[/tex]
[tex]x-1=-5x-10[/tex]
[tex]x+5x=-10+1[/tex]
[tex]6x=-9[/tex]
[tex]x=-9/6=-3/2[/tex]
We have two possible outcomes.
[tex] x-1=5x+10[/tex]
[tex]x-5x=10+1[/tex]
[tex]-4x=11[/tex]
[tex]x=-11/4[/tex]
Solution #2 [tex]x-1=-(5x+10)[/tex]
[tex] x-1=-(5x+10)[/tex]
[tex]x-1=-5x-10[/tex]
[tex]x+5x=-10+1[/tex]
[tex]6x=-9[/tex]
[tex]x=-9/6=-3/2[/tex]
We have two possible outcomes.